The impact of COVID-19 outbreak on otolaryngology practice, jordanian experience: A qualitative study. (February 2021) - Al Omari, Ahmad; Kanaan, Yazan; Nuseir, Amjad; Al-ashqar, Ra'ed; Al-Balas, Hasan; Hamarneh, Osama; Alzoubi, Firas
Abstract: Background: In response to the rapid spread of coronavirus disease 2019 (COVID-19) caused by "severe acute respiratory syndrome coronavirus 2" (SARS-CoV-2), many countries including Jordan have implemented strict lockdowns. These lockdowns were associated with temporary suspension of all outpatient clinics and all elective (Non emergent, non-oncologic) surgical procedures. Objective: We aimed to report the impact of COVID-19 outbreak on otolaryngology practice in Jordan. Methods: Retrospectively we reviewed all admissions to the otolaryngology wards of King Abdullah University Hospital during the lockdown and for the same dates for the year 2019, results were compared. Additionally, an online questionnaire was sent to a sample of Jordanian otolaryngologists in June 2020. The questionnaire was comprised of a series of multiple choice questions regarding each physician's participation in the treatment or screening of COVID-19 patients, the number of consultations during the lockdown, the numbers of elective and emergency surgical procedures performed during the lockdown and the effects the lockdown had on their practices, their patients conditions and teaching and training processes. The study was done in line with the criteria set by the Standards for Reporting Qualitative Research (O'Brien et al., September 2014) [12]. Strengths and weaknesses: In our study, we aimed to include the experience of all otolaryngology practitioners in Jordan, providing a comprehensive view of the lockdown effects on practice in the region. The data found is likely representative of lockdown effects on all departments, not just otolaryngological practice, and may be beneficial in providing a pathway to minimize any negative impact on patient care. However, our data may be limited due to its dependence on responses through a Whatsapp questionnaire, with no guarantee that the answers provided are fully accurate. It also may have a certain degree of sampling bias, as while the questionnaire was sent to all ENT practitioners in Jordan, answering it was totally optional, and so people who did not respond to the survey were not accounted for. Results: During the lockdown period in Jordan all outpatient clinics were closed, and all elective surgical procedures (non-emergency and non-oncologic procedures) were suspended. During the lockdown it was observed that there was a reduction in the number of admissions related to post-operative complications, head and neck abscesses & infections and foreign bodies related admission when compared to the same period of 2019. A total of 144 otolaryngologists have participated in the questionnaire part of the study. More than half of the participants (n = 80, 55.6%) reported providing 10 or less consultations during the lockdown, more than half of the them have not performed any emergency surgical procedures during the lockdown, and a total of 110 (76.4%) of the 144 participants reported having at least 1 patient whose condition worsened during the lockdown due to lack or delay in medical care. Conclusion: The COVID-19 pandemic, and the resultant lockdown period in Jordan has caused a significant shift in otolaryngological practice throughout the country, with a complete cessation of all outpatient clinics and elective surgical procedures and admissions, with activity being limited to oncological and emergency procedures only. These changes have already impacted the dynamics of patient care and might lead to a risk of diagnostic delays which will have severe impacts on patient's health. Highlights: SARS-CoV-2 is a highly contagious virus and can spread through both direct means (droplet and human-to-human transmission) and by indirect contact (contaminated objects and airborne contagion). In response to the rapid spread of coronavirus disease 2019 (COVID-19) caused by "severe acute respiratory syndrome coronavirus 2" (SARS-CoV-2), many countries including Jordan have implemented strict lockdowns The COVID-19 pandemic, and the resultant lockdown period in Jordan has caused a significant shift in otolaryngological practice worldwide